Observational Study on the Safety and Efficacy of Rituximab in Multiple Sclerosis: Insights from North-Eastern Iran: Rituximab Efficacy and Safety in MS: Iran - Saeidi, Morteza; Taheri, Naghme Sadat; Mohebrad, Negin; Pourbagher-Shahri, Ali Mohammad; Nahayati, Mohammadali (Iranian Journal of Pharmaceutical Sciences, 2025)
Multiple sclerosis (MS) is a chronic autoimmune and inflammatory disease that affects young people and causes demyelination and axon loss in the central nervous system. According to several studies, rituximab (RTX) reduces inflammation and relapse in patients with relapsing-remitting MS. This study aimed to evaluate the efficacy and safety of RTX in patients suffering from MS. MS patients were treated in the comprehensive MS clinic of Ghaem Hospital, Mashhad, Iran, and RTX administration was approved for them (1000 mg). Before initiating the study, demographic characteristics (e.g., age, gender, and type of MS disease), clinical variables (e.g., annual relapse rate [ARR] in the year before the intervention, Expanded Disability Status Scale (EDSS) score, and magnetic resonance imaging [MRI] findings), laboratory variables (e.g., complete blood count [CBC], liver and kidney function tests) for the patients were recorded. After the intervention, the variables were checked and re-recorded, and the patients were followed up at 6 and 12 months. In total, 50 patients with relapsing-remitting MS (RRMS), primary progressive MS (PPMS), or secondary progressive MS (SPMS) with mean age and treatment duration of 37.60±8.91 and 6.72±5.28 years, respectively, were included in the study. The results showed no significant difference among the three time periods regarding the mean disability level (P=0.73). Moreover, the mean ARR decreased significantly after the intervention (P=0.007). This study showed that RTX administration effectively reduces the ARR, and no significant safety issues were recorded. However, the results of this study could not prove RTX’s efficacy in preventing confirmed disability progression.